Analysis of Monzer Kahf's Thoughts on the Phenomenon of Consumption in Modern Society - Ranaswijaya, Ranaswijaya; soleha, soleha (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This study aims to describe the analysis of Monzer Kahf's thoughts on the phenomenon of consumption that occurs in today's society.Design/Method/Approach: Descriptive qualitative research with a literature review approach was used in this research. This approach was used because researcher only needed information, explanations and analysis to compile this research. The data was collected through observation and documentation while data analysis techniques used conclusion drawing techniques to obtain information objectively and systematically.Findings: The results show that Islam does not prohibit individuals from using goods to achieve satisfaction, but still regulates and limits their use so as not to violate sharia principles. A Muslim in consumption is based on obedience to Allah, needs, social justice, and freedom from sin. Therefore, a person's satisfaction in consumption is not solely based on the amount of goods consumed, but also considers whether the action is in accordance with religious teachings or not. Consumption done in order to fulfill Allah's commands and avoid His prohibitions will bring more meaningful satisfaction than merely pursuing worldly pleasures. In addition, Islam also prohibits israf and tabdzir in consumption, as these are considered inefficient and can harm one and others.Originality/Values: This research contributes to providing understanding in carrying out Islamic consumption in general and specifically based on Monzer Kahf's thoughts.